United States' Refusal to the International Criminal Court's Investigation of Crimes Against Humanity Conducted by Israel in Palestine - Muhamad Dafi Akbar; Davilla Prawidya Azaria (Lambung Mangkurat Law Journal, 2026)
This research examines the legal validity of the United States’ rejection of the International Criminal Court’s (ICC) investigation into alleged crimes against humanity committed in Palestine. The issue arises from the imposition of United States sanctions on ICC officials, despite the United States not being a State Party to the Rome Statute and its reliance on domestic legislation such as the American Servicemembers’ Protection Act of 2002. Using a normative juridical method, this study analyzes primary legal sources, including the Rome Statute, the Vienna Convention on the Law of Treaties, and ICC jurisprudence, alongside relevant secondary materials. Particular attention is given to the Appeals Chamber decision of 15 December 2025, which rejected Israel’s objection under Article 18 of the Rome Statute and confirmed the Prosecutor’s authority to proceed with the investigation into the situation in Palestine. The findings indicate that the ICC lawfully exercises territorial jurisdiction based on Palestine’s 2015 accession and Article 12(2)(a) of the Rome Statute, and that obligations arising from jus cogens and erga omnes norms render unilateral countermeasures legally ineffective. Furthermore, the study argues that sanctions targeting ICC judges and prosecutors may constitute improper interference with the administration of justice under Article 70 of the Rome Statute. The study concludes that such sanctions undermine the independence of the ICC, weaken the universality of international criminal accountability, and risk politicizing the enforcement of core international crimes.